Enhanced community capital from primary school feeding and agroforestry program in Kenya. (January 2017) - Borish, David; King, Nia; Dewey, Cate
Highlights: The impacts of a feeding program on a rural Kenyan community were examined. Household income was saved when children were fed at school. Agricultural knowledge improved and tree planting increased within the community. Social relations were enhanced within households and the community. Increased community involvement will support program sustainability. Abstract: This case study examines the impact of the Bwaliro Primary School feeding and agroforestry program on the human, financial, natural, and social capitals of the surrounding Bwaliro community in western Kenya. Additional to the targeted improvements in attendance and educational performance, program spillover effects likely included enhanced child health, community agroforestry knowledge, increased tree planting and diversity of crops and trees, saved household income, and improved relations within the family unit and among community members. Participants suggested that increasing the community's capacity to contribute to and collaborate with the school is necessary for program sustenance and for further community development.